Pelvico-Abdominal Plexiform Neurofibromatosis: Radiologic Clues to an Exceptional Presentation - Regina Primeylisa Dos Santos; Pande Putu Yuli Anandasari (Green Publisher Indonesia, 2026)
Plexiform neurofibroma is a rare subtype of benign neurofibroma that occurs almost exclusively in individuals with Neurofibromatosis type 1. The tumor develops from an abnormal proliferation of multiple components of a peripheral nerve and may arise in various parts of the body, although it most frequently involves the head, neck, pelvis, and extremities. In uncommon situations, NF1 may also present with localized or systemic manifestations within the abdomen and pelvis, which can resemble other pathological conditions and create diagnostic difficulties.This report focuses on plexiform neurofibroma occurring in an adolescent girl, an unusual presentation with significant clinical relevance. Both Neurofibromatosis type 1 and Neurofibromatosis type 2 are hereditary disorders characterized by the formation of benign tumors, with plexiform neurofibroma representing one of the less common tumor variants associated with these conditions. The case highlights the value of multimodality imaging—such as ultrasound, CT, and MRI—in establishing the diagnosis and monitoring disease progression.